ผลการให้คำปรึกษาแบบกลุ่มตามทฤษฎีการให้คำปรึกษา แบบผู้รับการปรึกษาเป็นศูนย์กลาง ของ Carl R. Rogers ต่อการปรับตัวด้านการเรียน ของนักศึกษา ระดับปริญญาตรี - เปรมกมล, ชวนพิศ; สุริยาศศิน, ศรีสมร (วารสาร ศึกษาศาสตร์ มมร, 2020)
การวิจัยกึ่งทดลองครั้งนี้ มีวัตถุประสงค์เพื่อ (1) เปรียบเทียบผลการให้คำปรึกษาแบบกลุ่มตามทฤษฎีการให้คำปรึกษาแบบผู้รับการปรึกษาเป็นศูนย์กลาง ของ Carl R. Rogers ต่อการปรับตัวด้านการเรียน ของนักศึกษาระดับปริญญาตรี ที่เข้าร่วมและไม่ได้เข้าร่วมรับการปรึกษาแบบกลุ่ม (2) เปรียบเทียบผลการให้คำปรึกษาแบบกลุ่มตามทฤษฎีการให้คำปรึกษาแบบผู้รับการปรึกษาเป็นศูนย์กลาง ของ Carl R. Rogers ต่อการปรับตัวด้านการเรียนของนักศึกษาระดับปริญญาตรี เป็นกลุ่มทดลอง ระหว่างก่อนการทดลอง และหลังการทดลอง (3) เปรียบเทียบผลการให้คำปรึกษาแบบกลุ่มตามทฤษฎีการให้คำปรึกษาแบบผู้รับการปรึกษาเป็นศูนย์กลาง ของ Carl R. Rogers ต่อการปรับตัวด้านการเรียน ของนักศึกษาระดับปริญญาตรี ระหว่าง หลังการทดลอง และเมื่อสิ้นสุดระยะการติดตามผล 2 สัปดาห์ กลุ่มตัวอย่างที่ใช้ในการวิจัย ได้แก่ นักศึกษาระดับปริญญาตรี ชั้นปีที่ 1 ภาคการศึกษาที่ 2 ปีการศึกษา 2560 มหาวิทยาลัยเทคโนโลยีราชมงคลสุวรรณภูมิ ที่มีคะแนนผลการเรียนต่ำกว่า 2.00 ในภาคเรียนที่ 1 มีคะแนนการปรับตัวด้านการเรียนในระดับต่ำ และมีความสมัครใจที่จะเข้าร่วมการทดลอง จำนวน 16 คน และทำการสุ่มอย่างง่ายเพื่อแบ่งเป็นกลุ่มทดลอง 8 คนและกลุ่มควบคุม 8 คน เครื่องมือที่ใช้ในการวิจัยประกอบด้วย แบบวัดการปรับตัวด้านการเรียนและโปรแกรมการให้การปรึกษาแบบกลุ่ม ตามทฤษฎีการให้คำปรึกษาแบบผู้รับการปรึกษาเป็นศูนย์กลาง ของ Carl R. Rogers วิเคราะห์ข้อมูลด้วยคอมพิวเตอร์ โดยใช้โปรแกรมสำเร็จรูปทางสถิติ ได้แก่ สถิติ Independent t–test และสถิติ Dependent t–test  ผลการวิจัย พบว่า (1) นักศึกษาระดับปริญญาตรี ที่เข้าร่วมและไม่ได้เข้าร่วมการปรึกษาแบบกลุ่มตามทฤษฎีการให้คำปรึกษาแบบผู้รับการปรึกษาเป็นศูนย์กลาง ของ Carl R. Rogers มีการปรับตัวด้านการเรียน แตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 (2) นักศึกษาระดับปริญญาตรี ที่ได้เข้าร่วมการให้คำปรึกษาแบบกลุ่ม ก่อนและหลังการเข้าร่วมรับการปรึกษาแบบกลุ่มมีการปรับตัวด้านการเรียน แตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 (3) นักศึกษาระดับปริญญาตรี ที่ได้เข้าร่วมการให้คำปรึกษาแบบกลุ่ม หลังการเข้าร่วมรับการปรึกษาแบบกลุ่มและเมื่อสิ้นสุดระยะการติดตามผล 2 สัปดาห์ มีการปรับตัวด้านการเรียน ไม่แตกต่างกัน In this quasi-experimental research investigation, the researcher compares (1) the effects of group counseling based on client – centered theory of Carl R. Rogers on learning adjustment of undergraduate students participating in group counseling with those who do not participate. The researcher also compares (2) the effects of group counseling based on client – centered theory of Carl R. Rogers on learning adjustment of undergraduate students is an experimental groups, prior to the commencement and after the completion of the experiment. Finally, furthermore, the researcher compares (3) the effects of group counseling based on client – centered theory of Carl R. Rogers on learning adjustment of undergraduate students after the completion of the experiment and at the end of the 2 –week follow-up period The sample population consisted of sixteen first-year undergraduate students with the GPA lower than 2.00 for the first semester of academic year 2017 at Rajamangala University of Technology Suvarnabhumi. The simple random sampling method was used to divide the students into an experiment group and a control group of eight each. The research instruments consisted of a form on learning adjustment and a group counseling program the effects of group counseling based on client – centered theory of Carl R. RogersThrough applications of a computer software program, the researcher analyzed the data collected by means of an independent t- test and a dependent t- test. Findings are as follows: (1) Undergraduate students the effects of group counseling based on client – centered theory of Carl R. Rogers on learning adjustment of undergraduate students participating in group counseling with those who do not participate on learning adjustment different at the statistically significant level of .05. (2) Undergraduate students who participated in group counseling before and after participating in group counseling, there is an adjustment in learning. Differing significantly at the level of .05 (3) Undergraduate students who participated in group counseling After joining the group counseling and at the end of the 2-week follow-up period, there is an adjustment of learning not different